Highly Sensitive Polydiacetylene Ensembles for Biosensing and Bioimaging - Huang, Qiong; Wu, Wei; Ai, Kelong; Liu, Jianhua (Frontiers in Chemistry, 2020)
Polydiacetylenes are prepared from amphiphilic diacetylenes first through self-assembly and then polymerization. Different from common supramolecular assemblies, polydiacetylenes have stable structure and very special optical properties such as absorption, fluorescence, and Raman. The hydrophilic head of PDAs is easy to be chemically modified with functional groups for detection and imaging applications. PDAs will undergo a specific color change from blue to red, fluorescence enhancement and Raman spectrum changes in the presence of receptor ligands. These properties allow PDA-based sensors to have high sensitivity and specificity during analysis. Therefore, the PDAs have been widely used for detection of viruses, bacteria, proteins, antibiotics, hormones, sialic acid, metal ions and as probes for bioimaging in recent years. In this review, the preparation, polymerization, and detection mechanisms of PDAs are discussed, and some representative research advances in the field of bio-detection and bioimaging are highlighted.